Environmental Law Policy in Industrial Waste Management - Azi Fachri Mandala (CV. Rayyan Dwi Bharata, 2023)
The environment is everything that is around humans and has a reciprocal relationship with one another. The opposite of the living environment is man-made which includes areas and also components that are heavily influenced by humans. What is studied is various laws and regulations, especially Law Number 32 of 2009 concerning Environmental Protection and Management, as well as other references. Law Number 32 of 2009 concerning Environmental Protection and Management stipulates that the quality of the environment which is decreasing day by day threatens human survival and can also cause global warming which increases climate change. Therefore, to avoid and also before the environment becomes increasingly damaged, it is important for humans to protect and preserve the environment so that it does not become extinct and destroyed because of the actions of the humans themselves.